2003
DOI: 10.1248/cpb.51.994
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Root Growth-Inhibitory Activity of 2- and 3-(Haloacetylamino)-3-(2-furyl)propanoic Acids

Abstract: Compounds of the chloroacetamide family are major preemergence herbicides for control of seedling grass in corn and soybean crops, and are among the most widely used herbicides in the world.1,2) For example, the thiophene derivative dimethenamid [2-chloro-N-(2,4-dimethyl-3-thienyl)-N-(2-methoxy-1-methylethyl)acetamide] (1) is used for control of annual grasses and certain broadleaf weeds, primarily in corn and soybeans and also in peanuts. [3][4][5][6][7] In addition, thenylchlor [2-chloro-N-(3-methoxy-2-thien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…5) Recently, we developed an improved preparation of racemic 2-amino-3-(furan-2-yl)propanoic acid (furylalanine) (7a), 6) and we used the same approach for synthesis of 2-(chloroacetamido)-3-(furan-2-yl)propanoic acid [N-(chloroacetyl)furylalanine] (7b) for the evaluation of plant growthinhibitory activity. We found that 7b inhibited the root growth of rape seedlings by about 51% at the concentration of 1.0ϫ10 Ϫ4 M. 7) As a continuation of that work, we have investigated the biological activity of various N-substituted 2-(2-chloroacetamido)-3-(furan-2-yl)propanamides (16)(17)(18).…”
mentioning
confidence: 99%
“…5) Recently, we developed an improved preparation of racemic 2-amino-3-(furan-2-yl)propanoic acid (furylalanine) (7a), 6) and we used the same approach for synthesis of 2-(chloroacetamido)-3-(furan-2-yl)propanoic acid [N-(chloroacetyl)furylalanine] (7b) for the evaluation of plant growthinhibitory activity. We found that 7b inhibited the root growth of rape seedlings by about 51% at the concentration of 1.0ϫ10 Ϫ4 M. 7) As a continuation of that work, we have investigated the biological activity of various N-substituted 2-(2-chloroacetamido)-3-(furan-2-yl)propanamides (16)(17)(18).…”
mentioning
confidence: 99%
“…6) We have recently reported that 2-(chloroacetylamino)-3-(furan-2-yl)propanoic acid (2) showed root growth-inhibitory activity towards rape seedlings. 7) As a continuation of that work, we have investigated a convenient route to a key intermediate, namely, racemic 3-(furan-2-yl)alanine (1a). This furan derivative (1a) has been synthesized in several ways, e.g., (i) diketopiperazine method, 8) (ii) hydantoin method, 9,10) (iii) rhodanine method, [11][12][13] and (iv) halomethylfuran-acylamidomalonate method.…”
mentioning
confidence: 99%